Alternative models of implementation Co rporate Social Responsibility (CSR) Rehabilitation Home Unlivable (RTLH) Sinarmas in Military Region VII / Wirabuana Makassar involving the public sector, private sector and civil society d early in perspective Gove - Iskandar, Deni; Haselman,; Hasniati,; Susanti, Gita (IJRDO - Journal of Social Science and Humanities Research, 2016)
In view of the science of public administration involvement of other actors outside the state (Non State) in managing public affairs known as the paradigm of governance. Governance refers to a process of policy-making and the process by which the policy was implemented with the involvement of the public sector (state/government), private sector (private) and civil society (community) in the process of making and implementing the policy ofthe. With the Law No. 40 taun 2007 on PT particular article 74 on social corporate responsibility (CSR) and Article 66 which requires the company is required to have a report from the program  CSR indicted, the phenomenon of CSR has become a public matter. With the paradigm a governance that must involve many actor in solving public problems and CSR has become a public matter in the presence of the law comes the question, how should the model ideal implementation or alternative models should be done in the implementation of CSR RTLH Sinarmas in Military Region VII /Wirabuana in the perspective of governance expected in a n involve the public sector, private sector as well as civil society. By viewing, Governance(Rhodes, 1996, S toker 1998, ADB 2000) public sector roles in strengthening corporate social responsibility Fox, Ward, Howard (2002) P enelitian will explain how an alternative model should be done in the implementation of CSR Sinarmas in Military Region VII / Wirabuana. The results showed that the model is empirical implementation of CSR Sinarmas in Military Region VII / Wirabuana not been carried out in accordance paradigm governanceIt can be seen from not any involvement of the role ofother actors, no system of supervision as well as the mechanism of a defense answers regarding accountability, transfarency, Responsibility and fairnes still found irregularities in implementing therefore researchers suggest a model alternative in the implementation of CSR RTLH Sinarmas in Military Region VII /Wirabuana involving the private sector and civil society in the governance perspective.